Intravenous Dexmedetomidine Administration Prior Anesthesia Induction With Propofol at 4°C Attenuates Propofol Injection Pain: A Double-Blind, Randomized, Placebo-Controlled Trial - Lu, Yayun; Gu, Yaping; Liu, Lihua; Tang, Xuefeng; Xia, Qing; Xu, Zhiyue (Frontiers in Medicine, 2021)
Background: Propofol injection pain, despite various interventions, still occurs during the anesthesia induction and causes intense discomfort and anxiety in patients. This study aimed to explore the effect of intravenous dexmedetomidine on propofol injection pain prior to anesthesia induction with propofol at 4ºC. Methods: A total of 251 patients (American Society of Anesthesiologists I–II) who underwent oral and maxillofacial surgery were randomly assigned to a combination group (n=63), lidocaine group (n=62), dexmedetomidine group (n=63), and placebo-control group (n=63); they received 0.5 ug/kg dexmedetomidine prior to anesthesia induction with propofol at 4ºC, 40 mg lidocaine, 0.5 ug/kg dexmedetomidine prior to anesthesia induction , and normal saline, respectively. Incidence of pain, pain intensity, and reaction to the pain stimulus were evaluated by using verbal categorial scoring (VCS), a numerical rating scale (NRS), and the Surgical Pleth Index (SPI), respectively. In addition, hemodynamic parameters such as heart rate (HR) and mean arterial pressure (MAP) were also measured. The VCS and NRS were evaluated at 5 seconds after propofol injection. In addition, SPI, HR, and MAP were evaluated at three time points (before anesthesia induction and 5 seconds and 30 seconds after propofol injection). Results: The incidence of pain in the combination group (51%) was significantly lower than that in the lidocaine group (71%) , dexmedetomidine group (67%), or placebo-control group (94%) (p＜0.001). VCS and NRS scores in the combination group were also lower compared with the other three groups (p＜0.001). The SPI of the combination group decreased significantly in comparison with the other three groups at 5 seconds after propofol injection (F=96.23, p＜0.001) and 30 seconds after propofol injection (F=4.46, p=0.005). Further comparisons between HR and MAP revealed no significant differences across the groups (p>0.05). Conclusion: Because of the sedative nature of dexmedetomidine and analgesic effect of low temperature, this study showed that intravenous dexmedetomidine prior to anesthesia induction with propofol at 4ºC is highly effective in attenuating the incidence and severity of pain during injection compared with lidocaine (40 mg), dexmedetomidine 0.5ug/kg) and placebo. This approach was not associated with any anesthesia complications.